Quality and efficiency of accounting information systems - SETYANINGSIH, S.D.; MULYANI, S.; AKBAR, B.; FARIDA, I. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT A good accounting information system, institution, or organization can increase its value through increasing quality and efficiency, especially in terms of supply chain efficiency and effectiveness, improving internal control structures, and improving decision making. This research was conducted using a survey questionnaire distributed to 51 employees who work in the Accounting Unit of Ministries and Institutions using the purposive sampling method. Structural equation modeling using the Lisrel 8.80 program was used to analyze the data. The results showed that the Accounting Information System Implementation had a significant positive effect on Organizational Performance through the Quality of Financial Reporting. RESUMEN Un buen sistema, institución u organización de información contable puede aumentar su valor aumentando la calidad y la eficiencia, especialmente en términos de eficiencia y efectividad de la cadena de suministro, mejorando las estructuras de control interno y mejorando la toma de decisiones. Esta investigación se realizó mediante un cuestionario de distribuido a 51 empleados que laboran en la Unidad de Contabilidad de Ministerios e Instituciones utilizando el método de muestreo intencional. Se utilizó el modelado de ecuaciones estructurales utilizando el programa Lisrel 8.80 para analizar los datos. Los resultados mostraron que la Implementación del Sistema de Información Contable tuvo un efecto positivo significativo en el Desempeño Organizacional a través de la Calidad de la Información Financiera.